Supported playgroups in schools: bonding and bridging family knowledge about transition to formal schooling. Issue 2 (4th March 2018) - McLean, Karen; Edwards, Susan; Evangelou, Maria; Lambert, Pamela
Abstract: Supported Playgroups in Schools (SPinS) are a new initiative in the Australian early childhood education landscape. SPinS are playgroups hosted by a playgroup coordinator co-located on a local school site. Research has identified positive benefits of playgroup participation for children and families. However, little is known about the potential for SPinS to contribute to families' knowledge about transition to formal schooling. This paper uses the social capital concepts of 'bonding' and 'bridging' to examine caregivers' perspectives on their participation in a SPinS with potential to build parental knowledge about their child's transition to formal schooling. Three main elements of caregivers' participation in SPinS with such potential are identified, and these elements are mapped into a continuum of low-to-high bonding and bridging relationships to illustrate the potential for SPinS to contribute to the development of increased knowledge about transition to formal schooling by families of young children.